1972
DOI: 10.1128/jb.109.1.34-43.1972
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Control of Serine and Glycine Biosynthesis in Saccharomyces

Abstract: Two of the three known metabolic pathways to serine and glycine have been shown to be present in prototrophic yeast strains, i.e., the phosphorylated pathway from glycolytic intermediates and the glyoxylate pathway from tricarboxylic acid cycle intermediates. Two serine-glycine auxotrophs ( ser1 and ser2 ) were found to be blocked in the phosphoglycerate pathway. The ser1 gene controls l -glutamate:phosphohydroxypyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
4

Year Published

1974
1974
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 20 publications
3
34
0
4
Order By: Relevance
“…Serine can be used for biosynthesis of glycine, cysteine and tryptophan in many organisms (Pizer, 1965;Ulane and Ogur, 1972;Largen and Belser, 1975;Kitabatake et al, 2000). In the present study, addition of glycine and cysteine, but not tryptophan, enhanced the growth of the crp mutants at levels similar to those observed with addition of serine.…”
Section: Effects Of Crpmt On Growth Of M Tuberculosis and M Bovis Bcgsupporting
confidence: 68%
“…Serine can be used for biosynthesis of glycine, cysteine and tryptophan in many organisms (Pizer, 1965;Ulane and Ogur, 1972;Largen and Belser, 1975;Kitabatake et al, 2000). In the present study, addition of glycine and cysteine, but not tryptophan, enhanced the growth of the crp mutants at levels similar to those observed with addition of serine.…”
Section: Effects Of Crpmt On Growth Of M Tuberculosis and M Bovis Bcgsupporting
confidence: 68%
“…In S. cerevisiae, the glycine pathway via Agx1p is repressed by glucose but is the major pathway during growth on nonfermentable carbon sources. Accordingly, the triple deletion mutant gly1 shm1 shm2, which lacks the two alternative glycine pathways, is a glycine auxotroph on glucose (Ulane & Ogur, 1972;Schl€ osser et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings, obtained with the recombinant enzymes in vitro, strongly suggested that the serine depletion observed in the ykl151cD mutant resulted from inhibition of the main serine synthesis pathway at the level of the first dedicated step by the high intracellular NADHX concentrations. As our in vitro results would predict complete inhibition of 3PGA oxidation at the NADHX concentrations reached in the ykl151cD mutant in postdiauxic phase (more than 100-fold higher than the concentrations needed to completely block the Ser33 activity in vitro), the residual serine pool measured in the mutant most likely derived from the glyoxylate route for serine synthesis [36,53]. Discovery of the extremely conserved, but apparently not essential, NAD(P)HX repair system [7] raised the question of its physiological relevance.…”
Section: Nad(p)hx Repair Deficiency Leads To Discrete Changes In Genementioning
confidence: 91%